Answer:56.8 inches
Step-by-step explanation:
For perimeter we must find the lengths of the 2 diagonal sides of the triangle which are the same because it is isosceles.
the triangle is cut directly in half so both halves of the base are 17/2
17/2 = 8.5
solve through pythagoren theorum
altitude^2 + (half of base)^2 = (diagonal length)^2
18^2 + (8.5)^2 = (diagonal length)^2
324 + 72.25 = (diagonal length)^2
396.3 = (diagonal length)^2
= diagonal length
diagonal length = 19.9
diagonal length + diagonal length + base = perimeter
19.9 + 19.9 + 17 = perimeter
56.8 inches = perimeter
The distance between starting and ending point is 34 miles.
Step-by-step explanation:
Given,
Car moves 16 miles to north then 30 mile to east.
It forms a right angle triangle.
The straight line distance from starting to ending point represents hypotenuse.
To find the distance between starting and ending point.
Formula
By <em>Pythagoras theorem,</em>
h² = b²+l² where h is the hypotenuse, b is base and l is the another side.
Taking, b=16 and l=30 we get,
h² = 16²+30²
or, h = ![\sqrt{256+900}](https://tex.z-dn.net/?f=%5Csqrt%7B256%2B900%7D)
or, h =
= 34
Hence,
The distance between starting and ending point is 34 miles.
-2y-4=4y-4
2) cancel 4 out on both sides
-2y=4y
3) divide both sides by -2
y=-2y
4) subtract both sides by -2y
y+2y=0
5)3y=0
6) divide by 3
Y=0
Hello there! The missing y-values are 12, 14, and 16.
Given all our x-values and two additional y-values, we can see that multiplying the x-value by 2 gives us the y-value. This is shown when x is 5 and 9, because multiplying 5 by 2 gave us 10, and multiplying 9 by 2 gave us 18. Because of this rule, we can multiply each given x-value by 2 to receive our y-value. Once solving, we also notice that the y-values all add by 2 to get the next factor as the data number increases. Hope this helps!
For this case we have the expression:
"the square root of 4" is represented algebraically as:
![\sqrt {4}](https://tex.z-dn.net/?f=%5Csqrt%20%7B4%7D)
Then, we can express the given statement as:
![3 \sqrt {4} -2 \sqrt {4} =](https://tex.z-dn.net/?f=3%20%5Csqrt%20%7B4%7D%20-2%20%5Csqrt%20%7B4%7D%20%3D)
They are similar terms, we can subtract:
![3 \sqrt {4} -2 \sqrt {4} = \sqrt {4} = \sqrt {2 ^ 2}](https://tex.z-dn.net/?f=3%20%5Csqrt%20%7B4%7D%20-2%20%5Csqrt%20%7B4%7D%20%3D%20%5Csqrt%20%7B4%7D%20%3D%20%5Csqrt%20%7B2%20%5E%202%7D)
By definition of power properties we have that:
![\sqrt [n] {a ^ n} = a ^ {\frac {n} {n}} = a](https://tex.z-dn.net/?f=%5Csqrt%20%5Bn%5D%20%7Ba%20%5E%20n%7D%20%3D%20a%20%5E%20%7B%5Cfrac%20%7Bn%7D%20%7Bn%7D%7D%20%3D%20a)
Then the expression is reduced to:
![\sqrt {2 ^ 2} = 2](https://tex.z-dn.net/?f=%5Csqrt%20%7B2%20%5E%202%7D%20%3D%202)
Answer:
![3 \sqrt {4} -2 \sqrt {4} = 2](https://tex.z-dn.net/?f=3%20%5Csqrt%20%7B4%7D%20-2%20%5Csqrt%20%7B4%7D%20%3D%202)